Upgrading the Ultraviolet Protection Factor of Cotton Fabrics Using Nanoparticles Synthesized from Plant Waste Extract and Cold Plasma Technique - Nafiseh Nasirzadeh; Reza Faridi-Majidi; Farideh Golbabaei; Mohammad Reza Monazzam Esmaielpour (Journal of Natural Fibers)
Wearing the right clothing can help reduce UV exposure and protect the skin from damages. The aim of this study was to upgrade the ultraviolet protection factor (UPF) of cotton fabrics using nanoparticles synthesized from plant waste extract and cold plasma technique. ZnO nanoparticles (ZnO-NPs) have been synthesized using sour-cherry pomace extract. For the adhesion of nanoparticles, two approaches were used: Citric acid and Cold plasma technique. Finally, the UPF was calculated based on spectroscopy data, before and after washing. The surface of fabrics and the air permeability characteristics were evaluated using instrumental methods. Peaks assigned for ZnO-NPs were confirmed by XRD. Spherical ZnO-NPs had an average size of 29.98 ± 9.5 nm, with the functional groups of O–H, C = O, C = C, and C–F. The UPF for uncoated fabrics, coated fabrics along with citric acid and plasma was 38.92, 566, and 658, respectively. After washing, the UPF for uncoated fabrics was constant, but it for coated samples had reduced to 540 and 616, respectively. Also, coated fabrics showed an increase in the air permeability. The coated cotton fabrics have excellent protection (+50) when compared to uncoated cotton fabrics. Also, cold plasma can lead to an upgrade of the UPF of cotton fabrics.